DAEE - 10 anos de experiência acumulada na exploração dos recursos hídricos subterrâneos - Aguiar, A. T. de; Andrade, E. de P.; Hirata, R. C. A.; da Silva, R. B. G. (Águas Subterrâneas, 1984)
indisponível